Introducing a Value Added Tax : Lessons from Ghana - Chapman, Emma (World Bank, Washington, DC, 2012)
In 1998 Ghana's government successfully introduced a value added tax (VAT). But this success followed a failed attempt in 1995, when the country's first VAT was repealed after just three and a half months. Ghana's experience provides several lessons for the successful introduction of a VAT-particularly the importance of recognizing public sensitivity to changes in the tax system and of securing public acceptance when introducing a VAT. A VAT's introductory rate has a big influence on public opinion, but so do public education and management of public expectations. In addition, political commitment- in terms of both an enabling macroeconomic environment and the enactment of legislation-is crucial for securing popular support and ensuring the timely introduction of a VAT.